The qualitative arm of the ATTUNE research in the Czech Republic: The methods, study design, sample, and life chart analysis - Petruželka, Benjamin; Laštovková, Jitka; Barták, Miroslav (Adiktologie, 2020)
BACKGROUND: Methamphetamine use is a long-term problem in the Czech Republic. The evidence describing the individual careers of different methamphetamine users is limited. AIMS: The aim of this study is to describe the methodological approach of the qualitative arm of the ATTUNE study in the Czech Republic and the first results of the analysis. METHODS: The data collection in this arm of the study was based on different instruments: offline and online screening instruments, a guide for semi-structured interviews, and life charts. Quasi-quantitative analysis of the data from the supporting data collection instruments (life charts and screening instruments) was conducted to produce a rich description of the stratified sample. SAMPLE: Six different groups of informants were predefined: dependent, remitted, frequent users, frequent ex-users, non-frequent users, and non-users. For each of the six groups five interviews were conducted, except dependent users (six interviews) and non-frequent users (four interviews). RESULTS: The results of the quasi-quantitative analysis showed the differences between the user groups. The results suggest that the remitted and dependent users are similar in most of the aspects that are described when compared to the other groups. The groups of non-frequent users and non-users seem to be different to all the other groups. Furthermore, the results were used to discuss the strengths and limits of different instruments that take empirical data into account. CONCLUSIONS: The article introduced the ATTUNE study to the Czech context and showed that the supporting data collection instruments (life charts and screening instruments) are helpful in providing a description of the stratified sample that is useful for further analysis and that these instruments are also practical for the data collection and allocation to groups of informants.